2012
DOI: 10.1007/s00068-012-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

Lodox/Statscan facilitates the early detection of commonly overlooked extracranial injuries in patients with traumatic brain injury

Abstract: The Lodox/Statscan can provide benefits for surveying extracranial injuries in patients with diminished level of consciousness. The Lodox/Statscan also emits a notably low dose of radiation and appears to be a relatively inexpensive adjunct to screen torso or extremity injuries in TBI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This indicates that false-positive fracture detection is uncommon using all modalities. Specificities are similar to those reported for adults in previous studies, (33,34,36,39,41) and similar to those reported for skull fractures in piglets (97.7% - 100.0%). (44) PPVs are high for all modalities and all regions (all above 80.0%) which indicates that a fracture detected by any modality is highly likely to indeed be a true-positive identification.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This indicates that false-positive fracture detection is uncommon using all modalities. Specificities are similar to those reported for adults in previous studies, (33,34,36,39,41) and similar to those reported for skull fractures in piglets (97.7% - 100.0%). (44) PPVs are high for all modalities and all regions (all above 80.0%) which indicates that a fracture detected by any modality is highly likely to indeed be a true-positive identification.…”
Section: Discussionsupporting
confidence: 90%
“…However, sensitivities for X-rays and Lodox in the present study are lower than those previously reported (70.0% for X-rays (57) and 100.0% for Lodox). (41) Sensitivities are, however, higher than those reported for piglets using all modalities (43.0% -58.0%), (23) except for the posterior limbs using X-rays. The moderate to high sensitivities for detecting limb fractures using all modalities is important since long bone fractures are common in instances of violent crime.…”
Section: Limb Fracturesmentioning
confidence: 65%
See 1 more Smart Citation
“…Wei et al [ 22 ] reported that the rate of missed distal bone fracture when using plain X-ray films is up to 7.6% in TBI. In an attempting to lower this incidence of missed injuries, Huang et al [ 10 ] conducted a clinical study with whole body X-rays with Lodox/ Statscan for early detection of commonly missed trauma in TBI. Their institutional data showed that the missed extracranial injuries in TBI were up to 39.1% while the whole body X-rays reduced this rate of missed bone fractures down to 1.6% with low cost and low radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The technology was developed to scan the entire body of mineworkers with sufficient resolution and speed but with a low X-ray dosage to prevent harm during daily screenings (2). In recent years, acute care settings such as emergency departments have begun implementing Lodox imaging to triage trauma patients (315). Additional applications in the emergency room have included arteriography (16), ventriculoperitoneal shunt visualization (17, 18), detection of urinary stones (19) or foreign bodies (20, 21), and pediatric imaging (2224).…”
Section: Discussionmentioning
confidence: 99%